Islamic Legal Perspectives on Digital Literacy Challenges in Muslim Family Parenting - Muhammad Aniq (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2026)
This article examines digital parenting challenges in Muslim families from the perspective of Islamic law, with particular attention to the concept of hadanah and the objectives of maqāṣid al-shari’ah. The rapid expansion of digital technology has transformed parenting patterns and created new risks for children, including exposure to harmful content, cyberbullying, digital addiction, and moral decline. Using a normative-juridical and library-based approach, this study analyzes how Islamic legal principles can guide parents in protecting children’s faith, intellect, soul, honor, and future generation in the digital age. The findings show that Islamic law provides a strong normative foundation for digital parenting through supervision, spiritual communication, digital rules, religious education, and parental role modeling. The study also argues that effective protection of Muslim children in the digital era requires collaboration between family, educational institutions, religious leaders, and the state. In this way, digital literacy becomes not only a technical skill but also a moral and spiritual responsibility grounded in Islamic values